2017
DOI: 10.11124/jbisrir-2016-003273
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and processes of clinical reasoning in nurses and factors related to its use: a scoping review protocol

Abstract: The objectives of the scoping review are to.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Furthermore, it has been proposed that diagnostic errors may arise from flaws in the thinking processes during clinical reasoning (Norman et al, 2017). Research has highlighted the strategies employed in the training of thinking processes that might improve clinical reasoning and decision making, hence leading to better quality in healthcare (Griffits et al, 2017;Gummesson et al, 2018;Lambe, O'Reilly, Kelly, & Curristan, 2016;Schmidt & Mamede, 2015).…”
Section: Research In Clinical Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been proposed that diagnostic errors may arise from flaws in the thinking processes during clinical reasoning (Norman et al, 2017). Research has highlighted the strategies employed in the training of thinking processes that might improve clinical reasoning and decision making, hence leading to better quality in healthcare (Griffits et al, 2017;Gummesson et al, 2018;Lambe, O'Reilly, Kelly, & Curristan, 2016;Schmidt & Mamede, 2015).…”
Section: Research In Clinical Reasoningmentioning
confidence: 99%
“…Clinical reasoning, a central component of healthcare professionals’ competence, comprises the thought process that guides medical practice (Eva, 2005 ; Rogers, 1983 ). Clinical reasoning includes a range of critical thinking, judgment, decision making and problem-solving skills (Ajjawi & Higgs, 2008 ; Eva, 2005 ; Griffits, Hines, Moloney, & Ralph, 2017 ; Gummesson, Sundén, & Fex, 2018 ; Norman, 2005 ; Rogers, 1983 ). Learning how to reason can be viewed as a thinking process prone to ‘disposition’, since clinical reasoning can be influenced by personal attitudes, cultural perspectives and preconceptions (McCarthy, 2003 ; Scheffer & Rubenfeld, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple terms are used to refer to how nurses use higher-level cognitive skills in practice (Griffits et al, 2017;Tyo & McCurry, 2019). Although they are often used interchangeably, problem solving, critical thinking, clinical reasoning, clinical decisionmaking, and clinical judgment skills have important differences that affect how they are taught and evaluated.…”
Section: Cognitive Domain Outcomesmentioning
confidence: 99%
“…A review of a wide range of literature related to clinical reasoning in nursing education implies the consensus on the importance of clinical reasoning skill in nursing students, [6][7][8] however, there is very little evidence regarding this concept in nursing education curriculum. 2,4,9,10 The literature review indicated that the concept of clinical reasoning was introduced to nursing discipline in 1960, 11 however, its definition and components remained unidentified in the field of nursing education. 12 Though the research on clinical reasoning in nursing education is a topic in evolution, yet it lacks a clear applicable conceptual definition in the research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…17 A literature review conducted by the authors revealed that in recent years, structural changes in the field of professional nursing 1,6,14,17,18 alongside the changes resulting from modifications in educational policies have been important factors contributing to the concept of clinical reasoning and its antecedents. 9,10,15 Nursing education experts similarly believe that simultaneously with the changes in professional and social fields, the consequences of this concept in professional nursing have changed 19,20 ; besides, this concept in nursing practice and training is being recognized as a process underlying professional development 20 that causes a positive transfer of students to the role of the professional nurse through increasing awareness and competence in nursing practice. 16 Given that more recent research in the field of in clinical reasoning have provided various characteristics, antecedents, and consequences for clinical reasoning based on the structural changes and educational conditions, a broader conceptualization of clinical reasoning in the field of nursing education would facilitate the exploration and identification of characteristics and factors related to reasoning in the clinical practice of nursing students and helps them to achieve a clear semantic understanding.…”
Section: Introductionmentioning
confidence: 99%